F.V. Yezerskiy Personality’s Influence on the Development of his Scientific Views - V. Ya. Sokolov; S. N. Karelskaia; E. I. Zuga (Учёт. Анализ. Аудит, 2025)
The paper explores accounting theories focusing on the influence of Fyodor Ezerskiy’s, one of the most famous Russian accountants, his identity and surroundings. The history of his triple Russian accounting is the subject of research both in our country and abroad. The study uses the prosopographical and archival research methods. The authors aim to analyze the works of F.V. Ezerskiy in comparison with similar works of his time. Russian triple-entry bookkeeping, as research shows, is a double-entry system variation where equity equals assets minus liabilities, mirroring English practices. And they are in no way related to the ideas of Ijiri’s triple-entry bookkeeping. Ezerskiy’s system originated from two sources: his War Office budgetary accounting experience and Johnson’s English accounting system. In order to spread it, he created conditions under which everyone knew it. Ezerskiy spurred debate among academic accountants on his system by critiquing double-entry bookkeeping and promoting his own in his journals. Ezerskiy’s courses trained over 15,000 accountants in Russia’s triple-entry bookkeeping system over 40 years. Also, he attracted like-minded supporters and sympathizers by establishing an accountant’s society, offering professional development and family-friendly activities. The system developed by Ezerskiy became not only his life’s work but also a way to earn money. Although the pioneering bookkeeper, who shunned traditional Italian double-entry methods, was famous, Ezerskiy was not unique. The authors’ analysis in this paper established that Ezerskiy’s system closely resembles the ideas of E. Dégrange (Sr.) — the creator of the so called an American accounting form. They simplified accounting by employing auxiliary registers and decreasing the number of general ledger accounts. The phrase “triple-entry bookkeeping” pre-dates Ezerskiy; Rodolphe Roupp’s book describes a system much like Dégrange’s. Like Ezerskiy, Roupp also noted that his triple-entry bookkeeping was necessary to avoid errors in the records. This doesn’t diminish Ezerskiy’s contributions; his era’s accounting systems were distinguished by the number of registers, not the number of accounts used. This is also characteristic of Ezerskiy’s system.